Dynamic pilot allocation scheme in massive MIMO system - Xin FANG; Xingxing LI; Haiyan CAO; Peng PAN; Yunju LIU (Dianxin kexue)
In order to solve the problem of the pilot contamination in multi-cell massive multiple input multiple output (MIMO) system,a dynamic pilot allocation scheme was proposed by analyzing the error of MMSE channel estimation.Users living in the fringe regions between the target cell and adjacent cells adopt the dynamicpilot allocation scheme,the rest of users are randomly pilot allocation to increase the average achievable sum rate of the downlink.The simulation results show that the proposed method can not only apparently improve the performance of the channel estimation,but also effectively improve the achievable sum rate of the downlink in the whole system.